2020
DOI: 10.1093/cvr/cvaa142
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of fibroblast activation protein provides atheroprotection

Abstract: Aims Fibroblast activation protein (FAP) is upregulated at sites of tissue remodelling including chronic arthritis, solid tumours, and fibrotic hearts. It has also been associated with human coronary atherosclerotic plaques. Yet, the causal role of FAP in atherosclerosis remains unknown. To investigate the cause-effect relationship of endogenous FAP in atherogenesis, we assessed the effects of constitutive Fap deletion on plaque formation in atherosclerosis-prone apolipoprotein E (Apoe) or lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…To date only 2 studies have been published, where constitutive FAP knockout had a modest effect on bleomycin-induced pulmonary fibrosis progression 16 or on protection from the development of atherosclerosis. 44 However, constitutive FAP knockout cannot be compared with pharmacological inhibition with our highly specific FAPi. 45 , 46 , 47 Thus, Panaro et al 45 found that, although specific pharmacological FAP inhibition improved glucose tolerance in mice with diet induced obesity, FAP knockout did not protect these mice from insulin resistance, suggesting that elimination of FAP activity rather than constitutive genetic loss of FAP is essential for the beneficial effect.…”
Section: Discussionmentioning
confidence: 99%
“…To date only 2 studies have been published, where constitutive FAP knockout had a modest effect on bleomycin-induced pulmonary fibrosis progression 16 or on protection from the development of atherosclerosis. 44 However, constitutive FAP knockout cannot be compared with pharmacological inhibition with our highly specific FAPi. 45 , 46 , 47 Thus, Panaro et al 45 found that, although specific pharmacological FAP inhibition improved glucose tolerance in mice with diet induced obesity, FAP knockout did not protect these mice from insulin resistance, suggesting that elimination of FAP activity rather than constitutive genetic loss of FAP is essential for the beneficial effect.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting proteins, expressed by activated fibroblasts could attenuate vascular inflammatory responses and ameliorate vascular disease, including atherosclerosis. Recently, it was discovered that inhibition of expression or activity of fibroblast activation protein (FAP), that is expressed in activated but not in quiescent fibroblasts and was found to be associated with atherosclerotic plaques, can attenuate progression of atherosclerosis by increasing plaque stability in experimental mice models of atherosclerosis [74]. The potential role of fibroblasts during atherosclerosis progression.…”
Section: The Role Of Fibroblasts In Atherosclerosis and Potential Fibroblast-targeted Therapymentioning
confidence: 99%
“…Cancer-associated fibroblasts (CAFs) are central components of the tumor microenvironment (TME) and play crucial roles in tumor development, immune suppression, and cancer invasion. A notable biomarker highly expressed in CAFs is the fibroblast activation protein (FAP), a type II membrane-bound glycoprotein. FAP is upregulated in numerous epithelial carcinomas, wound healing, arthritis, atherosclerotic plaques, and fibrosis, with little expression in normal tissues. Thus, it is considered a promising target for cancer diagnosis and therapy. …”
Section: Introductionmentioning
confidence: 99%